Safety of allogeneic hematopoietic stem cell transplantation in beta‐thalassemia patients with chronic hepatitis C infections treated at a pediatric center. (17th June 2019) - Ramgopal, Archana; Lauko, Adam; Rotz, Seth; Hanna, Rabi
Abstract: The outcome of allogeneic HCT in patients previously infected with HCV is a widely debated topic and rarely reported in the pediatric and young adult age group given the small population of affected patients. New medications directly targeting HCV have induced virologic cures for over 90% of patients, and their use in the pretransplant setting may improve outcomes for patients infected with HCV. We describe two patients with transfusion‐dependent beta‐thalassemia major who underwent matched sibling donor bone marrow transplantation, one with a myeloablative regimen and one with a reduced‐intensity conditioning regimen. Allogeneic HCT appears feasible in patients with HCV infection that clear viremia prior to conditioning therapy and with a reduced‐intensity conditioning regimen. Further investigation is warranted to better define transplant risks in this population.